Promotion strategies and future research & development needs on industrialised building systems - Salihuddin Radin Sumadi; Ng, Johnson Weng Kuan; S. L., Sim; C. M., Tham; National Seminar on Industrialised Building System (2001 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2001)
03